Decision Support System for Covid-19 Aid Recipients using VIKOR method - Lengkong, Salvius Paulus (Jurnal Teknik Informatika, 2020)
Abstract — Covid19 is a disease caused by corona virus. The World Health Organization has declared covid19 a pandemic. Many of the negative impacts of covid19 have been felt by the world community, especially Indonesia. Many people lost their jobs. The Indonesian government provides support to the community through various ministries, agencies and related institutions. The distribution of this aid must be right on target so the purpose of providing this aid can be felt by people who are really affected by covid19. This study conducted a system design for covid19 beneficiaries using VIKOR method. The results of this study indicate that a decision support system using the VIKOR method was successfully designed. The design of this system is also expected to assist decision makers in providing assistance to communities affected by covid19. Keywords — Covid19; DSS; SPK; VIKOR.  Abstract — Covid19 merupakan penyakit yang disebabkan oleh corona virus. World Health Organisation menetapkan covid19 sebagai pandemi. Banyak dampak negatif oleh covid19 ini dirasakan oleh masyarakat dunia khususnya Indonesia. Banyak masyarakat kehilangan pekerjaan mereka. Pemerintah Indonesia memberikan bantuan kepada masyarakat melalui berbagai Kementerian, Dinas dan lembaga terkait. Pemberian bantuan ini harus tepat sasaran supaya tujuan pemberian bantuan ini dapat dirasakan oleh masyarakat yang memang benar-benar terdampak covid19. Penelitian ini melakukan perancangan sistem untuk penerima bantuan covid19 dengan menggunakan metode VIKOR. Hasil penelitian ini menunjukkan bahwa sistem pendukung keputusan menggunakan metode VIKOR berhasil dirancang. Rancangan sistem ini juga diharapkan dapat membantu pembuat keputusan dalam hal memberikan bantuan bagi masyarakat yang terdampak covid19.Kata kunci — Covid19; DSS; SPK; VIKOR.